The effect of dexamethasone in laparoscopic abdominal surgery - a review on inflammatory markers for stress response - Karsten Kaiser; Sven Hoedt Karstensen; Alexandros Nikolaou Valsamides Valorenzos; Kristian Als Nielsen; Thomas Strøm; Ismail Gögenur; Lukas Balsevicius; Finn Friis Lauszus (BMC Surgery)
Abstract Background We aimed to perform a review focused on the effects of dexamethasone on markers of surgical stress in the context of laparoscopic abdominal surgery. Methods This review was registered at PROSPERO. Published reports were evaluated with COVIDENCE, focusing on randomized controlled trials from the MEDLINE, EMBASE and CENTRAL databases. Studies were included if they compared a single intravenous dose of dexamethasone to placebo given preoperatively to adult patients undergoing laparoscopic or robotic assisted abdominal surgery under general anesthesia. The outcome of interest was inflammatory response in general and in particular c-reactive protein. Results Out of 588 references, we included seven studies. These involved a variety of surgical procedures, with cholecystectomies being the most common, and included mixed gender populations except in studies on gynecology surgery. Due to the heterogeneity in outcomes and the low number of studies no meta-analysis was performed. Levels of c-reactive protein was 38-60 % lower at 24 to 48 hours postoperatively with a dose of 8 mg dexamethasone compared to placebo, predominantly in cholecystectomy cases. Post-trial calculation indicates that the power of these studies ranged between 60% and 95%. Conclusion Our review may indicate a reduction of surgical stress in laparoscopic abdominal surgery measured by c-reactive protein, when a single dose of dexamethasone is administered. Trial registration PROSPERO: CRD 42024421062.